Synthesis and Characterization of Nickel(II) and Copper(II) Complexes with 3-(p-Chlorobenzyl)-4-(p-hydroxy-m-methoxybenzylidenamino)-1H-1,2,4-triazole-5-one - Arslantas, Ali; Isiklar, Mustafa; Yuksek, Haydar (Asian Journal of Chemistry, 2011)
In the paper, the nickel(II) and copper (II) complexes of 3-(p-chlorobenzyl)-4-(p-hydroxy-m-methoxybenzylidenamino)- 1H-1,2,4-triazole-5-one have been synthesized and characterized by elemental analyses, IR, UV-vis, 1H NMR spectra.